Analisis Kondisi Fisik Atlet Junior Bolavoli Club H2R Pekanbaru - ., Alnisa Riskya Putri Maharani; ., Oki Candra (CV. ITTC INDONESIA, 2023)
The purpose of this research is to find out how the physical condition of the H2R Pekanbaru Volleyball Club Athletes. The population and sample in this study were all H2R Pekanbaru Volleyball Athletes, totaling 36 athletes. The instrument used in this research is an instrument test consisting of a Flexometer, Running, Push Up and Hand Daynamometer test. Based on the results of research that has been done after conducting data analysis, it can be concluded that as much as 40% of the Physical Conditions of the Pekanbaru H2R Volleyball Club Athletes are in the Less category. Meanwhile, as much as 60% of the Physical Conditions of the Pekanbaru H2R Club Athletes were in the sufficient category.